Outcome of Different Preemptive Analgesia Modalities in Patients Undergoing Total Knee Replacement Surgeries: A Prospective Randomized Study - Narendra Vaidya; Gourav S. Pawar; Anup P Gadekar; Nilesh A. Patil; Pravin Rameshrao Kutemate; Mohit Kolhapure (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Many analgesic innovations are used to reduce the level of pain post total knee replacement (TKR) surgeries; however, none has been proven to be the optimum choice till now. The use of preemptive analgesia (PA) is still a controversial topic; however, still, it has managed to prevent altered pain perception and pain amplification after surgery. Hence, the objective of this study was to assess the pain score in patients undergoing TKR using different preemptive anesthesia modalities. Materials and Methods: A total of 105 patients were enrolled in the study and were equally divided into three groups. Group 1 and Group 2 were given tablet pregabalin 75 mg, tablet paracetamol 1 g, and tablet aceclofenac 100 mg orally 1 day before surgery, and on the day of surgery, before incision, Group 1 received injection paracetamol 1 g and injection dexamethasone 8 mg intravenously; Group 2 received injection paracetamol 1 g, injection dexamethasone 8 mg, injection tramadol 50 mg, and injection MgSo4 1 g intravenously; And Group 3 received only iPACK. Results: The average Visual Analog Scale score was the least in Group 2, followed by Group 1 and Group 3 (P < 0.001). The average Ropivacaine dose and postoperative Ropivacaine duration were the least in Group 2, followed by Group 1 and Group 3 (P < 0.001). Patients in Group 2 were able to mobilize early compared to Group 1, whereas patients in Group 3 took more time for mobilization compared to Groups 1 and 2. Tourniquet pain was least in Group 2, followed by Group 1 and Group 3. Conclusion: PA was found to reduce the severity of pain and inflammation after knee replacement surgery, resulting in reduced development of chronic pain after surgery. As well significant relief from tourniquet pain was seen, which ultimately helped the patient in early mobilization.